Malerei des zwanzigsten Jahrhunderts : Kunstsammlung Nordrhein-Westfalen - Schloss Jägerhof Düsseldorf. - Schmalenbach, Werner; Kunstsammlung Nordrhein-Westfalen, Düsseldorf (Köln : Verlag M. DuMont Schauberg, 1968)
Antes, Horst ; Arp, Hans ; Bacon, Francis ; Baumeister, Willi ; Bazaine, Jean ; Beckmann, Max ; Bissier, Julius ; Braque, Georges ; Burri, Alberto ; Carra, Carlo ; Chagall, Marc ; de Chirico, Giorgio ; Delaunay, Robert ; Derain, André ; Dubuffet, Jean ; Ernst, Max ; Feininger, Lyonel ; etc.
Katalog der Erwerbungen 1962-1968, Kunstsammlung Nordrhein-Westfalen, Düsseldorf, 1968
boek